Budaya Patriarki dan Akses Perempuan dalam Pendidikan - Nursaptini Nursaptini; Muhammad Sobri; Deni Sutisna; Muhammad Syazali; Arif Widodo (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2019)
This paper aims to describe the patriarchal culture and women's access to education. The method used in this research is literature study from various sources such as books, journals, reports and data from the Central Statistics Agency. The results of this study are that patriarchal culture is inherent in a society that considers that the primary education should be boys. This causes women's access to education to be hampered due to cultural problems that exist in the community. This situation can be seen based on data on the percentage of literacy for women totaling 83.42 while men 91.86. This data is also supported by the data of the Human Development Index for men reaching 75.43 while the Human Development Index for women is 68.63. This data shows the level of education of women, especially in higher education is low. This reality certainly contradicts the goal of national education which does not differentiate access to education based on gender, all of whom are entitled to education.